2005
DOI: 10.1074/jbc.m409471200
|View full text |Cite
|
Sign up to set email alerts
|

Akt2 Phosphorylates Ezrin to Trigger NHE3 Translocation and Activation

Abstract: Initiation of Na؉ -glucose cotransport in intestinal absorptive epithelia causes NHE3 to be translocated to the apical plasma membrane, leading to cytoplasmic alkalinization. We reported recently that this NHE3 translocation requires ezrin phosphorylation. However, the kinase that phosphorylates ezrin in this process has not been identified. Because Akt has also been implicated in NHE3 translocation, we investigated the hypothesis that Akt phosphorylates ezrin. After initiation of Na ؉ -glucose cotransport, Ak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
91
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(98 citation statements)
references
References 62 publications
6
91
0
1
Order By: Relevance
“…6C 1 ). When HT29 cells were incubated with LY-294002, previously used as a pharmacological inhibitor of Akt phosphorylation (22), plus glucose and LPS, we observed a nuclear translocation of NF-B comparable to LPS-treated cells, confirming the role of Akt phosphorylation in the pathway leading to NF-B inhibition by glucose (Fig. 6C 2 ).…”
Section: Sglt-1-driven Inhibition Of Nf-b Activation Is Mediated By Aktsupporting
confidence: 48%
See 2 more Smart Citations
“…6C 1 ). When HT29 cells were incubated with LY-294002, previously used as a pharmacological inhibitor of Akt phosphorylation (22), plus glucose and LPS, we observed a nuclear translocation of NF-B comparable to LPS-treated cells, confirming the role of Akt phosphorylation in the pathway leading to NF-B inhibition by glucose (Fig. 6C 2 ).…”
Section: Sglt-1-driven Inhibition Of Nf-b Activation Is Mediated By Aktsupporting
confidence: 48%
“…Akt phosphorylation may be induced by SGLT-1 activation; in fact, Na ϩ -glucose cotransport mediated by SGLT-1 leads to a complex signal transduction pathway in which activation of p38 MAPK leads to Akt activation. Hu et al (23) have reported that the transport by the apical Na ϩ -glucose cotransporter SGLT-1 triggers translocation of NHE3 to the plasma membrane by activation of p38 MAPK, Akt2, and ezrin, whereas Shiue et al (22) suggested that inhibition of Akt using inhibitors prevents ezrin phosphorylation after initiation of Na ϩ -glucose cotransport. Moreover, Guha and Mackman (25) recently reported that the PI3K pathway in monocytes suppresses both MAPKs and NF-B cascades in response to LPS, resulting in decreased production of TNF-␣.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 These data, therefore, showed that MLCK-mediated MLC phosphorylation was necessary for Na ϩ -glucose cotransport-induced tight junction regulation. However, as subsequent work has identified a complex cascade of kinases that are activated by Na ϩ -glucose cotransport, [35][36][37][38] it was not clear whether MLCKmediated MLC phosphorylation alone was sufficient to regulate tight junction permeability.…”
Section: Barrier Function Can Be Regulated By Physiological Stimulimentioning
confidence: 99%
“…None of the polarized intestinal epithelial cell lines available today express detectable levels of transepithelial Na + -dependent glucose transport, which has been attributed to a deficiency of surface expression of SGLT-1 ( [Turner et al, 1996] and [Kipp et al, 2003]). In these transfected cells, the expression of SGLT-1 protein on the apical membrane is associated with functional Na + -dependent uptake of glucose, and physiological transduction pathways in response to SGLT-1 activation ( [Turner et al, 1996], [Shiue et al, 2005] and [Hu et al, 2006]). These cells were seeded in 8-well chamber slides (4 × 10 5 cells/well; Lab-Tek, Nalge Nunc, Rochester, NY), 24-well plates (10 6 cells/well; Costar, Corning Inc., Corning, NY), 6-well plates (6 × 10 6 cells/well, Costar) and 12-well transwells, which contained 1 cm 2 semipermeable filter membrane with 0.4 μm pores (10 6 cells/well, Costar) and grown to confluency for 1 week at 37 °C with 5% CO 2 and 96% humidity for experiments.…”
Section: Cell Culture Modelmentioning
confidence: 99%